Perubahan Gaya Kepemimpinan Dalam Meningkatkan Motivasi Kinerja Guru - Yakin, Moh. Ainul (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2023)
Leadership is an ability or strength within a person to influence others in terms of work, in order to achieve common goals. A strong leader seeks to be responsible to subordinates about the implementation of common goals. In order for each member to be responsible, all member participate in all activities, planning, organizing, monitoring, and evaluating. Each member has a valuable ability in an effort to achieve a common goal. Changes in leadership and collaboration are expected to motivate teacher performance in the spirit of working to achieve common goals. This study uses a qualitative approach, with a descriptive type. The location of this research is MAN Sampang. Data collection techniques using observation, interview, and documentation. The data analysis technique uses data reduction, data presentation, and conclusions. The result of this study indicate that the change in leadership style used by the principal understands the background of its members, has a clear goal in leadership change and the right strategy. The leadership style strategy used by the principal is openness in making decisions in implementing a program, implementing school based management aimed at improving school quality, and having a strong control system. Barriers to changes in leadership style, different individual cultural backgrounds, individual cultural character, nature, and work discipline among school members.